(untitled) (Academia Journal of Medicine, 2026)
Background: The infrazygomatic crest (IZC) is a preferred extra-alveolar site for orthodontic bone screw placement, offering dense bicortical bone and predictable anchorage. However, anatomical variations in IZC dimensions across different vertical facial growth patterns remain debated, and comprehensive data on second molar sites are limited. This study aimed to assess IZC bone thickness at multiple sites and angulations in patients with different vertical facial growth patterns to establish evidence-based guidelines for safe screw insertion. Aim: To determine IZC bone dimensions across different vertical facial growth patterns, identify optimal insertion sites and angulations, guide screw length selection, and evaluate gender-based differences. Materials and Methods: This cross-sectional study analyzed CBCT scans of 90 subjects (18-30 years) equally divided into average-growing, horizontal-growing, and vertical-growing groups. IZC bone thickness was measured at six sites bilaterally: mesiobuccal root of first molar (MB), distobuccal root of first molar (DB), proximal region between first and second molars (PR), and second molar region (MB2 and DB2), at insertion angulations of 65° and 70°. Measurements were performed using Carestream 9600 CBCT with CS 3D imaging software. Statistical analysis employed one-way ANOVA, post-hoc tests, and paired t-tests (p0.05). Second molar sites (MB2 70°: 3.72±0.92 mm; DB2 70°: 3.34±0.85 mm) showed moderate bone availability. Measurements at 70° were consistently greater than at 65° (p